100 TONS PER HOUR, WHAT IS NEXT? LET US COMPARE AND ANALYZE CHARACTERISTICS OF THE LATEST MODELS OF HIGHLY PRODUCTIVE COMBINE HARVESTERS - Burlaka, O. A.; Yakhin, S. V.; Padalka, V. V.; Burlaka, A. О. (Scientific Progress & Innovations, 2021)
The main characteristics of the latest models of combine harvesters of well-known world companies and brands: Claas Lexion 8900 Terra Trac; New Holland CR 9.80; Case IH Axial-Flow 9240; John Deere X 9110; Fendt IDEAL 10T; T-1000 have been studied and compared in the article. According to the results of the survey, it has been determined that: 1. The productivity of the latest combine harvesters of such brands is within the limits of 40…80 t/h approaching the mark of 100 t/h. The structural weight of such combine har-vesters is within the limits of 20…22 t. The capacity of the hopper fluctuates within 12,500…18,000 l. And it is approximately up to 12…17 t of additional weight at the hopper completely loaded with grain, and ac-cordingly, pressure increase on the soil through basic movers. Moreover, the problem of soil excessive com-paction is solved through the use of a semi-tracked movement. Effective highly productive use of combines of Claas, New Holland, Case, John Deere, Fendt companies and brands is possible under the condition of ap-plying them in combination with the tractors aggregating trailers- grain trucks. 2. Is it necessary to further increase the productivity of combine harvesters by increasing their size? The issue remains open and disput-able. Quite interestingly, the problem was solved in the USA by an ordinary farmer – Ben Dillon. He pro-posed a new architectural and layout scheme for the construction of a highly productive Tribine T-1000 combine harvester. In this model, the modular design was applied, the hopper is the back module – the trail-er, and the capacity of the hopper is increased to 35 m3. Unloading is carried out directly into the truck body at the edge of the field. The combine’s design consists of two half-frames. Controlled rear wheels allow the use of “crab motion” at moving, which reduces soil compaction. The innovations of Claas, New Holland, Case, John Deere, Fendt are aimed at developing autonomous robotized farm machinery. Tribine innova-tions, in addition to robotics, are aimed at following environmentally friendly farming systems. When choos-ing a modern combine harvester or tractor, it is possible to recommend Ukrainian farmers the multi-criteria assessment and give preference to complex agricultural machinery of one brand, which will further facilitate solving problems with technical service and use. And whether the combine harvester operator of the future will be in the cabin during the harvesting, or will control the machine remotely, time will show.